2017
DOI: 10.1002/ajmg.b.32529
|View full text |Cite
|
Sign up to set email alerts
|

FMR1 genotype interacts with parenting stress to shape health and functional abilities in older age

Abstract: This study investigated the association of genotype (CGG repeats in FMR1) and the health and well-being of 5628 aging adults (mean age = 71) in a population-based study. Two groups were contrasted: aging parents who had adult children with developmental or mental health disabilities (n = 785; the high-stress parenting group) and aging parents of healthy children who did not have disabilities (n = 4843; the low-stress parenting group). There were significant curvilinear interaction effects between parenting str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 51 publications
(71 reference statements)
4
18
0
Order By: Relevance
“…Historically, examination of behavioral phenotypes associated with FMR1-related variability (e.g., CGG repeat length) have largely focused on individuals with full mutation fragile X syndrome or the premutation, with some exceptions (10,11,16,78). Many prior assessments of cognition associated with the FMR1 gene involved group comparisons, typically between PM carriers and those with modal numbers of CGG repeats (2,4,5,16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, examination of behavioral phenotypes associated with FMR1-related variability (e.g., CGG repeat length) have largely focused on individuals with full mutation fragile X syndrome or the premutation, with some exceptions (10,11,16,78). Many prior assessments of cognition associated with the FMR1 gene involved group comparisons, typically between PM carriers and those with modal numbers of CGG repeats (2,4,5,16).…”
Section: Discussionmentioning
confidence: 99%
“…Of additional importance is the examination of environmental circumstances that may in uence phenotypic variation. Prior work suggests that stress, such as parenting a child with a disability, may uniquely in uence health outcomes across the CGG range (10). The present study aimed to characterize environmental and genetic predictors of self-reported cognitive function, speci cally executive function and memory, across the CGG repeat range.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of additional importance is the examination of environmental circumstances that may influence phenotypic variation. Prior work suggests that stress, such as parenting a child with a disability, may uniquely influence health outcomes across the CGG range (16). The present study aimed to characterize environmental and genetic predictors of self-reported cognitive function, specifically executive function and memory, across the CGG repeat range.…”
Section: Introductionmentioning
confidence: 98%
“…However, the CGG repeat is highly polymorphic, ranging from as few as 6 repeats to over 200 (9)(10)(11)(12)(13). A small body of literature highlights the importance of evaluating the possibility of involvement of CGG repeats continuously across this range with respect to both biological (9,14,15) and behavioral phenotypes (16,17). Thus, consideration of the FMR1 CGG repeat number continuously across the range below FXS has the potential to elucidate phenotypic variation at the population-level.…”
Section: Introductionmentioning
confidence: 99%